Combustion aerosols from mineral oil industrial fires: Physicochemical characterization and toxicity in bronchial epithelial cells at the air-liquid interface - C. Méausoone; T. Rogez-Florent; C. Castilla; L. Chevalier; C. Bouzar; P. Cardinael; T. Legeard; S. Tisse; J. Yon; F. Portet-Koltalo; E. Varea; B. Patte-Rouland; et al. (Environmental Pollution, 2026)

Gill ionocytes of the Lake Magadi tilapia (Oreochromis Alcolapia grahami), an extremophilic teleost native to a highly alkaline environment - Jonathan M. Wilson; Chris M. Wood; Pierre Laurent; Claudine Chevalier; Patrícia G. Ferreira; Kevin V. Brix; Gudrun DeBoeck; Harold L. Bergman; Adalto Bianchini; Lucas Feijó Bianchini; John N. Maina; Ora E. Johannsson; et al. (Cell and Tissue Research, 2026)

Paul Tapponnier, deciphering the Earth's crust deformation history in the rocks and landscapes - A. Replumaz; J.-P. Avouac; M.-L. Chevalier; Y. Klinger; C. Lasserre; P.H. Leloup; J. Liu-Zeng; G. Peltzer; J. van der Woerd; X. Xu (Tectonophysics, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

WITHDRAWN: Paul Tapponnier, deciphering the Earth's crust deformation history in the rocks and landscapes - A. Replumaz; J.-P. Avouac; M.-L. Chevalier; Y. Klinger; C. Lasserre; P.H. Leloup; J. Liu-Zeng; G. Peltzer; J. van der Woerd; X. Xiwei (Tectonophysics, 2026)

Using a comprehensive donor and host dataset to decipher the heritability and genetic architecture of pearl traits in the black-lipped oyster (Pinctada margaritifera) - L. Benestan; C. Massault; E. Vigouroux; O. Chevalier; D.B. Jones; D.R. Jerry; J. Le Luyer (Aquaculture, 2026)

Spondias tuberosa Arruda (Anacardiaceae) ethanolic leaf extract as a source of natural products inhibiting quorum sensing and pyocyanin production in planktonic Pseudomonas aeruginosa - A.S. Tareau; P.E. Bodet; J.R. Guedes da Silva Almeida; M. Barreau; O. Lesouhaitier; A. Tahrioui; R. Gonçalves de Oliveira Junior; R. Grougnet; P. Sitarek; L. Quintans-Junior; K. Baranger; S. Chevalier; et al. (Phytochemistry Letters, 2025)

No deformation propagation outward of the plateau across the Yalong Thrust Belt in Southeast Tibet - P. Pitard; A. Replumaz; P.H. Leloup; M.-L. Chevalier; S. Wang; M. Bai; X. Ou; M. Bernet; M. Balvay; E.R. Sobel; A. Vezinet; C. Gautheron; et al. (Tectonophysics, 2025)

P24-08 Chronic exposure to low-doses of maneb and manganese alters differentiation and lipid accumulation in hepatocytes in vitro - L. Chevalier; S. Pierre; M. Dufresne; M. Marceau; C. Pinteur; A. Corlu; B. Le Magueresse-Battistoni; P. Loyer (Toxicology Letters, 2025)

P08-12 Exposure to commercial copper-based nanopesticide reshapes chironomid-associated microbiota and alters host life history traits - L. Evariste; T. Moura; F. Chapeau; F. Candaudap; G. Le Roux; L. Chevalier; C. Larue; M. Barret; E. Pinelli; E. Houdeau; L. Gauthier; B. Lamas; et al. (Toxicology Letters, 2025)

A multi-model approach to the spatial and temporal characterization of the African Humid Period - William D. Gosling; Manuel Chevalier; Markus L. Fischer; Marjolein Holewijn; Jemma Finch; Graciela Gil-Romera; Trevor Hill; Alfred Houngnon; Michela Leonardi; Andrea Manica; Stefanie Kaboth-Bahr (Quaternary International, 2025)

Modelling the population dynamics of Rift Valley fever virus mosquito vectors in the western Mediterranean Basin - Alex Drouin; Thomas Balenghien; Benoit Durand; Carles Aranda; Amal Bennouna; Ali Bouattour; Said C Boubidi; Annamaria Conte; Sarah Delacour; Maria Goffredo; Oumnia Himmi; Grégory L'Ambert; et al. (Ecological Modelling, 2025)

Long-term impact of embryonic exposure to ethinylestradiol and clotrimazole on behavior and neuroplasticity in zebrafish (Danio rerio) - M. Blanc-Legendre; L. Guillot; L. Chevalier; C. Malleret; K. Le Menach; P. Pardon; H. Budzinski; F. Brion; S. Sire; P. Coumailleau; T.D. Charlier; E. Pellegrini; et al. (Environmental Toxicology and Pharmacology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P21-62 The copper-based nanopesticide Kocide 3000® worsens development of colitis in mice as a function of sex, and disrupts the intestinal barrier function in an enteroid-derived epithelial cell monolayer model from mouse gut organoids - E. Casale; Y. Malaisé; C. Cartier; E. Gaultier; L. Chevalier; T. You; S. Dupont; E. Houdeau; B. Lamas (Toxicology Letters, 2024)

Influence of the Rhone River intrusion on microplastic distribution in the Bay of Marseille - A. Alcaïno; L. Vidal; L. Licari; C. Paillès; S. Conrod; J. Dauvier; C. Chevalier; C. Pinazo; M. Grelaud; P. Ziveri (Regional Studies in Marine Science, 2024)

Uncovering the endemic circulation of rabies in Cambodia - Maylis Layan; Laurent Dacheux; Philippe Lemey; Kirstyn Brunker; Laurence Ma; Cécile Troupin; Philippe Dussart; Véronique Chevalier; James L. N. Wood; Sowath Ly; Veasna Duong; Hervé Bourhy; et al. (Molecular Ecology, 2023)
In epidemiology, endemicity characterizes sustained pathogen circulation in a geographical area, which involves a circulation that is not being maintained by external introductions. Because it could potentially shape the design of public health interventions, there is an interest in fully uncovering the endemic pattern of a disease. Here, we use a phylogeographic approach to investigate the endemic signature of rabies virus (RABV) circulation in Cambodia. Cambodia is located in one of the most affected regions by rabies in the world, but RABV circulation between and within Southeast Asian countries remains understudied. Our analyses are based on a new comprehensive data set of 199 RABV genomes collected between 2014 and 2017 as well as previously published Southeast Asian RABV sequences. We show that most Cambodian sequences belong to a distinct clade that has been circulating almost exclusively in Cambodia. Our results thus point towards rabies circulation in Cambodia that does not rely on external introductions. We further characterize within‐Cambodia RABV circulation by estimating lineage dispersal metrics that appear to be similar to other settings, and by performing landscape phylogeographic analyses to investigate environmental factors impacting the dispersal dynamic of viral lineages. The latter analyses do not lead to the identification of environmental variables that would be associated with the heterogeneity of viral lineage dispersal velocities, which calls for a better understanding of local dog ecology and further investigations of the potential drivers of RABV spread in the region. Overall, our study illustrates how phylogeographic investigations can be performed to assess and characterize viral endemicity in a context of relatively limited data.

Contamination of planktonic food webs in the Mediterranean Sea: Setting the frame for the MERITE-HIPPOCAMPE oceanographic cruise (spring 2019) - Marc Tedetti; Jacek Tronczynski; François Carlotti; Marc Pagano; Sana Ben Ismail; Cherif Sammari; Malika Bel Hassen; Karine Desboeufs; Charlotte Poindron; Sandrine Chifflet; Amel Bellaaj Zouari; Moufida Abdennadher; et al. (Marine Pollution Bulletin, 2023)

Genomic analysis of a parasite invasion: Colonization of the Americas by the blood fluke Schistosoma mansoni - Roy N. Platt; Winka Le Clec'h; Frédéric D. Chevalier; Marina McDew‐White; Philip T. LoVerde; Rafael Ramiro de Assis; Guilherme Oliveira; Safari Kinung'hi; Amadou Garba Djirmay; Michelle L. Steinauer; Anouk Gouvras; Muriel Rabone; et al. (Molecular Ecology, 2022)
Schistosoma mansoni , a snail‐borne, blood fluke that infects humans, was introduced into the Americas from Africa during the Trans‐Atlantic slave trade. As this parasite shows strong specificity to the snail intermediate host, we expected that adaptation to South American Biomphalaria spp. snails would result in population bottlenecks and strong signatures of selection. We scored 475,081 single nucleotide variants in 143 S. mansoni from the Americas (Brazil, Guadeloupe and Puerto Rico) and Africa (Cameroon, Niger, Senegal, Tanzania, and Uganda), and used these data to ask: (i) Was there a population bottleneck during colonization? (ii) Can we identify signatures of selection associated with colonization? (iii) What were the source populations for colonizing parasites? We found a 2.4‐ to 2.9‐fold reduction in diversity and much slower decay in linkage disequilibrium (LD) in parasites from East to West Africa. However, we observed similar nuclear diversity and LD in West Africa and Brazil, suggesting no strong bottlenecks and limited barriers to colonization. We identified five genome regions showing selection in the Americas, compared with three in West Africa and none in East Africa, which we speculate may reflect adaptation during colonization. Finally, we infer that unsampled populations from central African regions between Benin and Angola, with contributions from Niger, are probably the major source(s) for Brazilian S. mansoni . The absence of a bottleneck suggests that this is a rare case of a serendipitous invasion, where S. mansoni parasites were pre‐adapted to the Americas and able to establish with relative ease.

Characterization of functionalized bentonite as nanocarrier of salicylic acid with protective action against Pseudomonas syringae in tomato plants - Andrea Y. Mansilla; María F. Salcedo; Silvana L. Colman; Merari T. Chevalier; Matias R. Lanfranconi; Vera A. Alvarez; Claudia A. Casalongué (European Journal of Plant Pathology, 2020)

Sizes, condition factors and sex ratios of the scattered populations of the small cichlid fish, Alcolapia grahami, that inhabits the lagoons and sites of Lake Magadi (Kenya), one of the most extreme aquatic habitat on Earth - John N. Maina; Geraldine D. Kavembe; Michael B. Papah; Reatlegile Mashiteng; Chris M. Wood; Adalto Bianchini; Lucas F. Bianchini; Harold L. Bergman; Ora E. Johannsson; Piere Laurent; Claudine Chevalier; Rodi O. Ojoo (Environmental Biology of Fishes, 2019)

A high‐resolution record of Holocene climate and vegetation dynamics from the southern Cape coast of South Africa: pollen and microcharcoal evidence from Eilandvlei - Lynne J. Quick; Brian M. Chase; Michael Wündsch; Kelly L. Kirsten; Manuel Chevalier; Roland Mäusbacher; Michael E. Meadows; Torsten Haberzettl (Journal of Quaternary Science, 2018)
The southern Cape is a particularly dynamic region of South Africa in terms of climate change as it is influenced by both temperate and tropical circulation systems. This paper presents pollen and microcharcoal data generated from a sediment core extracted from the coastal lake Eilandvlei spanning the last ∼8900 years. With an average sample resolution of 57 years, this record represents the highest resolution record of Holocene vegetation change from the region. The data indicate that cool, seasonal and moderately dry conditions characterized the Wilderness Embayment from ∼8900 to 8000 cal a BP . Afrotemperate forests expanded from ∼8000 cal a BP until 4700 cal a BP . This humid period is followed by indications of more arid and seasonal conditions until 3500 cal a BP . A long‐term increase in forest taxa suggests steadily increasing moisture availability across the late Holocene. Strong affinities are noted with records from more tropical regions of South Africa, suggesting that tropical systems are of importance in maintaining higher moisture availability in the region. An important mechanism of climate change is the Agulhas Current, which transmits what appears to be a localized signal of tropical variability to the southern Cape coast.

A population of mitochondrion-rich cells in the pars recta of mouse kidney - M. S. Forbes; B. A. Thornhill; C. I. Galarreta; R. L. Chevalier (Cell and Tissue Research, 2016)

Hydrological variability of major French rivers over recent decades, assessed from gauging station and GRACE observations - L. Chevalier; B. Laignel; N. Massei; S. Munier; M. Becker; I. Turki; A. Coynel; A. Cazenave (Hydrological Sciences Journal, 2014)

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Air breathing in Magadi tilapia Alcolapia grahami , under normoxic and hyperoxic conditions, and the association with sunlight and reactive oxygen species - O. E. Johannsson; H. L. Bergman; C. M. Wood; P. Laurent; D. G. Kavembe; A. Bianchini; J. N. Maina; C. Chevalier; L. F. Bianchini; M. B. Papah; R. O. Ojoo (Journal of Fish Biology, 2014)
Observations of the Magadi tilapia Alcolapia grahami in hot, highly alkaline Lake Magadi revealed that they air breathe not only during hypoxia, as described previously, but also during normoxia and hyperoxia. Air breathing under these latter conditions occurred within distinct groupings of fish (pods) and involved only a small proportion of the population. Air breathing properties (duration and frequency) were quantified from video footage. Air breathing within the population followed a diel pattern with the maximum extent of pod formation occurring in early afternoon. High levels of reactive oxygen species ( ROS ) in the water may be an irritant that encourages the air‐breathing behaviour. The diel pattern of air breathing in the field and in experiments followed the diel pattern of ROS concentrations in the water which are amongst the highest reported in the literature (maximum daytime values of 2·53–8·10 µM H 2 O 2 ). Interlamellar cell masses ( ILCM ) occurred between the gill lamellae of fish from the lagoon with highest ROS and highest oxygen levels, while fish from a normoxic lagoon with one third the ROS had little or no ILCM . This is the first record of air breathing in a facultative air‐breathing fish in hyperoxic conditions and the first record of an ILCM in a cichlid species.

Trimetazidine demonstrated cardioprotective effects through mitochondrial pathway in a model of acute coronary ischemia - L. Dehina; F. Vaillant; A. Tabib; B. Bui-Xuan; Ph. Chevalier; N. Dizerens; C. Bui-Xuan; J. Descotes; V. Blanc-Guillemaud; L. Lerond; Q. Timour (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Transepithelial potential in the Magadi tilapia, a fish living in extreme alkalinity - Chris M. Wood; Harold L. Bergman; Adalto Bianchini; Pierre Laurent; John Maina; Ora E. Johannsson; Lucas F. Bianchini; Claudine Chevalier; Geraldine D. Kavembe; Michael B. Papah; Rodi O. Ojoo (Journal of Comparative Physiology B, 2012)